Present Religious Tendencies in Italy - Puglisi, Mario (The journal of religion, 1923)
To a superficial observation the opening years of this century would have suggested a religious exhaustion in the Italian spirit. The old religion was neglected until the war produced a temporary revival of interest among the soldiers. Two tendencies were evident, one toward mysticism, the other toward a revision of values in terms of social life. The crisis after the war was a religious crisis; men turned to Romanticism, materialistic Monism, Socialism, and Fascism as substitutes for the old religion. The philosophic interpretation of the new loyalty to the state was given by "Actual Idealism." The Catholic reaction came to terms with Fascism and enlisted many important intellectuals. The reaction seems successful. With the assent of the Fascisti the Catholic attack upon Masonry, Protestantism, and materialistic Monism has reduced them to silence. Two great spiritual currents are evident-the Catholic reaction and the vague religiousness centered about the state. Yet the spiritual quest takes a score of strange forms and the liberal forces work silently and in secret.